Virgin portraits. - Carl, Klaus (Parkstone International, 2011)
During the Renaissance, Italian painters would traditionally depict the wives of their patrons as Madonnas, often rendering them more beautiful than they actually were. Over centuries in religious paintings, the Madonna has been presented as the clement and protective mother of God. However, with the passing of time, Mary gradually lost some of her spiritual characteristics and became more mortal and accessible to human sentiments. Virgin Portraits illuminates this evolution and contains impressive works by Michelangelo, Caravaggio, Rubens, Fouquet, Dalí, and Kahlo.